S35 Efficacy and safety of the direct switch from various previous treatments to glycopyrronium or indacaterol/glycopyrronium in patients with moderate copd: the crystal study. (15th November 2016) - Vogelmeier, C; Aalamian-Mattheis, M; Greulich, T; Marin, J M; Castellani, W; Similowski, T; Ninane, V; Gaga, M; Lane, S; Nunez, X; Patalano, F; Clemens, A; et al.
Abstract : Introduction and objectives: In contrast to clinical trials, changes to new therapies in clinical practice occur without any washout period. The CRYSTAL study was designed to mimic clinical practice. Patients with symptomatic, non-frequently exacerbating, moderate COPD treated with various drugs were directly switched to glycopyrronium 50 μg (GLY) or indacaterol/glycopyrronium 110/50 μg (IND/GLY). Lung function and symptoms were evaluated. Methods: CRYSTAL was a prospective, multicentre, 12-week, randomised, pragmatic, open-label trial. Patients were recruited into 4 Groups according to previous medication and symptoms (mMRC) and randomised to a direct switch to GLY or IND/GLY vs. continuation of baseline therapy (3:1). Co-primary objectives were superiority of GLY vs. previous SABA and/or SAMA, non-inferiority of GLY vs. previous LABA or LAMA, and superiority of IND/GLY vs. LABA, LAMA and LABA+ICS regarding trough FEV1 and transition dyspnoea index (TDI) at Week 12. Due to slow recruitment, Groups A and B were prematurely discontinued at the time of completion of Groups C and D. Results: Of the 4, 389 patients randomised, 2, 159 patients received IND/GLY (C2: n = 811; D2: n = 811) or continued their previous treatment (LABA + ICS C1: n = 269; LABA or LAMA D1: n = 268). IND/GLY provided superior improvement in trough FEV1 at Week 12 vs. LABA + ICS (treatment difference (Δ) = 71 mL, p < 0.0001) and LABA or LAMA (Δ = 101 mL, p < 0.0001). IND/GLY also improved TDI vs. LABA + ICS (Δ = 1.10 units, p < 0.0001) and vs. LABA or LAMA (Δ = 1.26 units, p < 0.0001). Significantly more patients on IND/GLY reached the minimally clinically important difference (MCID) of 100 mL for trough FEV1 and 1 point for TDI vs. comparators (Table 1 ). In the Groups A and B that were underpowered due to sample size, GLY was superior to previous SABA and/or SAMA and was non-inferior to previous LABA or LAMA on trough FEV1 and TDI (Table 1 ). GLY and IND/GLY were well tolerated. Conclusions: In the pragmatic CRYSTAL trial, IND/GLY demonstrated superior improvement in lung function (trough FEV1) and dyspnoea (TDI) after 12 weeks, in symptomatic patients with moderate COPD and a history of up to 1 exacerbation in the previous year, after direct switch from previous treatment with either LABA+ICS or with a LABA or LAMA.